The Histone Database - Sullivan, Steven (Oxford University Press, 2002)
Histone proteins are often noted for their high degree of sequence conservation. It is less often recognized that the histones are a heterogeneous protein family. Furthermore, several classes of non-histone proteins containing the histone fold motif exist. Novel histone and histone fold protein sequences continue to be added to public databases every year. The Histone Database (http://genome.nhgri.nih.gov/histones/) is a searchable, periodically updated collection of histone fold-containing sequences derived from sequence-similarity searches of public databases. Sequence sets are presented in redundant and non-redundant FASTA form, hotlinked to GenBank sequence files. Partial sequences are also now included in the database, which has considerably augmented its taxonomic coverage. Annotated alignments of full-length non-redundant sets of sequences are now available in both web-viewable (HTML) and downloadable (PDF) formats. The database also provides summaries of current information on solved histone fold structures, post-translational modifications of histones, and the human histone gene complement.